Cluster of Differentiation 5 (CD5) Levels in the Plasma of Children with Autism Spectrum Disorder (ASD) - Halepoto, Dost Muhammad; Alhowikan, Abdulrahman Mohammed; Ayadhi, Laila Al (Journal of the College of Physicians and Surgeons--Pakistan, 2017)
To investigate the cluster of differentiation 5 (CD5) plasma levels and their association with childhood autism rating scale (CARS) in subjects with autism spectrum disorder (ASD) compared to age and gender matched healthy controls, and to explore the link between CD5, severity, and autoimmunity in autism. Case-control study. Autism Research and Treatment Center, Al-Amodi Autism Research Chair, Department of Physiology, Faculty of Medicine, King Khalid University Hospital, King Saud University, Riyadh, Saudi Arabia, from October 2014 to May 2015. CD5 levels were determined in the plasma of thirty-one (31) patients using enzyme-linked immunosorbent assay (ELISA), categorized as mild-moderate and severe as indicated by their Childhood Autism Rating Scale (CARS) score and compared to thirty-three (33) age and gender-matched control samples. The preliminary data indicated that children with severe autism (n=12), exhibited significantly (p=0.02) higher plasma level of CD5 [0.55 (0.14-12) pg/ml {median (interquartile range=IQR)}] than those of normal controls [n=33, 0.29 (0.08-0.79) pg/ml {median (IQR)}] and children with mild to moderate autism [n=19, 0.26 (0.13-1.42) pg/ml, {median (IQR)}, p=0.08]. However, there was no significant difference between the CD5 levels of children with mild to moderate autism and normal controls (p = 0.62). Diagnoses of autistic children based on the CARS score >30. Disease severity and the CARS score, which represent stereotyped patterns of behavior in children with autism, were positively correlated (r = 0.43, p = 0.02). The high CD5 plasma levels in patients with severe ASD, probably indicated that CD5 might be implicated in the physiology of autism. However, this finding should be treated with caution until further investigations are performed with larger populations to determine whether the increase in plasma CD5 levels is a mere consequence of autism or it plays a pathogenic role in the disease.